Content and form in the Rauf Parfi triads - Mahliyo Raximboyeva Omonboy qizi (Genius Journals, 2022)
For poetic speech, the dependence of content and form is important. In poetic discourse, the content is reflected in the idea reflected in it. (Four, Three, Five) Jehovah's Witnesses would be pleased to discuss these answers with you. We also encounter poems written in a variety of forms in the work of Ryan Perfufu
Keywords: Ryan Perfufu; poetic speech